Constitutionalism Concept in Implementation of Indonesian State Administration - Adhe Ismail Ananda (Jurnal Daulat Hukum, 2021)
The study in writing this paper is the essence of understanding constitutionalism in the context of the administration of the constitutional system. Constitutionalism for modern countries is a necessity. In the understanding of constitutionalism, the constitution is the embodiment of the highest law that must be obeyed by all components of the state. Writing the paper aims to explore further the philosophical meaning of this understanding of Constitutionalism. That in the concept and understanding of Constitutionalism, there are three things that become its essence. First, there is a limitation of power. Second, the exercise of power is carried out based on a general agreement that is crystallized into the constitution, and Third, the exercise of power always requires accountability within the framework of the constitution.